(3Yed eMeO Hf GdUHGM ddSGYGJ GdeHShWI HGdgfOSI aj Ci Ebdje CQOJs - (3GdMSf Hf eMeO Hf GdUHGM GdHRGQ GdRYaQGfqj GdHZOGOj, GHf GdnqUnqHGM,J (B259 (3g` s
(3ChdgG (B:s
(3hef gPg GdCdI fSJNQL SYI TQb GdHQhL hebOGQ fgGQgG hCReGf cd SGYI ef fgGQ gPg GdHQhL s
(3BNQgG (B:s
(3ebOGQ GdfgGQ ef OGFQI fUa bWQgG MSH JeGe Gdejd hjaYd ai SGFQ GdHQhL hGdYed ceG aYdfG ai HQL GdLOi dSGYGJ GdSQWGf cdgG hbO Je GdYed Ef TGA Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHY hGdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B212 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B284s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs